Biochemical and planimetric investigations of hydrophilic creams containing ceramides or dexpanthenol on the model of chemical burns - Butko, Yaroslava; Tishakova, Tetyana (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Chemical burns of the skin are common type of injuries both in private life and in industries. Local treatment of chemical burns using wound healing creams and ointments is predominant. Hydrophobic wound healing medicinal products dominate the Ukrainian pharmaceutical market but their hydrophobic base disturbs the healing process of skin. The aim of this work was biochemical and planimetric investigation of treatment efficacy of chemical burns with hydrophilic creams containing ceramides and dexpanthenol. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The experiments were performed on 30 rats weighing 190–220 g. In a rat skin burn model, animals were exposed to 9% acetic acid solution. Treatment was initiated after wound appearance and included application of creams containing ceramides and dexpanthenol. The effectiveness of treatment was estimated using planimetric parameters, such as: surface area of necrotic tissue (S, mm2) and cumulative reparative effect. Levels of the biochemical markers such as total protein, creatinine, C-reactive protein (CRP) and content of SH-groups were measured in the rats’ blood serum. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. It was established that cream developed with ceramides and cream with dexpanthenol exhibits reparative properties at the level of 29% and 4.5%, respectively. Biochemical investigations demonstrated the treatment efficacy of creams containing ceramides and dexpanthenol. In terms of CRP level and content of SH-groups, the therapeutic action of cream with dexpanthenol was highly significant by a factor of 1.45 and 1.35, respectively in contrast to the cream with ceramides. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Using the chemical burn model and results of planimetric and biochemical research it was found that cream with ceramides and cream with dexpanthenol exhibit wound-healing properties. In-depth study on the wound-healing mechanism of investigated creams with the aim of creating effective hydrophilic creams for use in burn treatment is prospective.